Az első női rendezők Magyarországon - Porogi Dorka (Symbolon)
The First Women Directors in Hungary This thesis focuses on the careers of women directors in 20th-century Hungary. Its purpose is to serve as a fundamental database and provide inspiration for future sociological, theatre historical, professionalization, and gender studies. Firstly, it examines the proportion of women who pursued theatre directing as a profession in Hungary and remained in the field. Subsequently, it delves into the careers and biographies of five directors from the first half of the century.